PENGARUH PENAMBAHAN ABU CANGKANG BEKICOT PADA SEMEN RAMAH LINGKUNGAN TERHADAP KUAT TEKAN MORTAR - Kurniawan, Achendri M.; Sulistiana, Devita (Jurnal Qua Teknika, 2018)
Blitar Regency is one of the strange culinary centers, among which are processed various foods from snail base ingredients, ranging from kripik, sate oseng-oseng and so on as well as the existence of Blitar district is one of the rice barns in East Java. With the existence of Blitar district as a snail-based culinary producer and one of the rice barns in East Java, this is not spared from several problems, such as the disposal of snail shells in the river and burning of rice straw in rice fields which both will cause environmental damage. This study aims to examine the use of snail shell ash and rice straw ash as a substitute material for cement in mortar mixtures against mortar compressive strength. The research method used was the experimental method by mixing fine aggregate main ingredients with snail shell ash and rice straw ash then testing the compressive strength. The results of the compressive test with the addition of the percentage of snail shell shell turned out to increase by 54.78%.